International education and development culture, context and narrative - Stephens, David (Routledge, Taylor & Francis Group, 2019)
"This book draws on international contexts to provide an innovative and comprehensive critique of efforts to improve schooling in the global South. It provides a critical examination of the macro 'stories' of development and international education over the past fifty years, paying particular attention to Western discourses, tensions between Western and indigenous models of development, and the emergence of new forms of educational provision and methods of learning; it examines the role narrative can play, looking at the stories of individual decision makers and the opportunities and challenges of using these for research, teaching and policy-making purposes"...